Child Insanity in England, 1845-1907 - Taylor, Steven. author. aut Link
XV, 188 p.
Keywords: This book explores the treatment, administration, and experience of children and young people certified as insane in England during the nineteenth and early twentieth centuries. It uses a range of sources from Victorian institutions to explore regional differences, rural and urban comparisons, and categories of mental illness and mental disability. The discussion of diverse pathways in and out of the asylum offers an opportunity to reassess nineteenth-century child mental impairment in a broad social-cultural context, and its conclusions widen the parameters of a ‘mixed economy of care’ by introducing multiple sites of treatment and confinement. Through its expansive scope the analysis intersects with topics such as the history of childhood, institutional culture, urbanisation, regional economic development, welfare history, and philanthropy. .